Meadowlands : a wetlands survival story - Yezerski, Thomas. (Farrar, Straus, Giroux, 2011)
The history of the Meadowlands, from its pristine state, to its gradual transformation by European settlers, to the pollution caused by industrialization, and the changes brought by environmental organizations striving to protect it.